DAMPAK BISNIS ONLINE TERHADAP FLUKTUASI PENJUALAN DI KOPERASI DALEM SELATAN (KDS) KAMILAH WILAYAH FATIMATUZZAHRO’ PONDOK PESANTREN NURUL JADID - H. Najiburrahman Wahid; Nur Halima (Nurul Jadid University, 2018)
This research is motivated by the development of times that are very rapid and increasingly modern so as to provide a boost to system changes both in terms of transactions, sales and marketing. The rise of virtual commerce or what is often called Online Business has a big influence on trade in the real world, as happened in our KDS in the Fathimatuzzahra ’PP region. Nurul Jadid. Before the online business that entered the KDS pesantren we experienced an increase in sales. However, after the existence of an online business that is increasingly prevalent in boarding schools causing fluctuations in sales at KDS, we are.This research was carried out to find out: (1) the impact that arises with the existence of an online business against fluctuations in sales in the KDS cooperative. (2) Steps of KDS cooperatives We are in maintaining consumer interest.Online business is a business whose trade is connected through the internet network. Sales fluctuations are the rate of dynamic change in the supply or production of producer goods within a certain period of time. Whereas KDS We are a business unit of pesantren which is different in nature from kopresai in general. This research is a type of qualitative research. This study chose a business unit in the Fatimatuzzahro region in the Nurul Jadid Islamic Boarding School. The technique of collecting data uses observation, interviews and documentation. The validity of the data is tested by triangulation. Data analysis techniques in the form of data collection, data reduction, data presentation and conclusion. After carrying out the research, the researcher concluded that the impact arising from the proliferation of Online sales was the decrease in KDS income. We were based on the monthly sales report of KDS. We were. and the steps taken to overcome the problem of decreasing income in our KDS are by increasing the promotion strategy, lottery coupons and price discounts.